Energy Poverty Impact on the Economics of Indonesia Using ARDL Approach - Wan, Ling Chin; Gaik, Tay Kim; Hwang, Goh Hui (International Journal of Integrated Engineering, 2020)
Energy poverty is a global threat to human development path. This study is about the cointegration relationship between energy poverty and the economy of Indonesia for the period of 1995 to 2014. Autoregressive Distributed Lag (ARDL) model and vector error correction model (VECM) were used in this study to study the cointegration and causality analysis. Unit root test and stability test were adopted to increase the reliability and accuracy of the model. The analysis shows that parity purchase power (PPP) has a positive relationship with inflation (INF) in both long-run and short-run. Result shows in long-run, the increment of 1% for both energy consumption (EC) and PPP will result -1.12% and 0.032% effect respectively towards inflation in Indonesia. While for 1% increase in energy consumption is expected to give 1.5297% increment on inflation in short-run cases. Granger causality test shows only unidirectional causality between parity purchase power and inflation in both the long-run and short-run. Energy consumption only shows unidirectional causality toward inflation in the long-run. Overall mean increase of PPP or EC has a single direction influence on the inflation rate. The study can aid policy planning in eradication energy poverty.